The Oncogenic Human Papillomavirus Involvement as a Risk Factor of Measles, Mumps, and Rubella Vaccine Immunotherapy Failure in Anogenital Warts - Achdiat PA; Ismiranty D; Hindritiani R; Rizqandaru T; Usman HA; Maharani RH (International Medical Case Reports Journal)
Pati Aji Achdiat,1 Dyah Ismiranty,1 Reti Hindritiani,1 Trustia Rizqandaru,1 Hermin Aminah Usman,2 Retno Hesty Maharani1 1Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Bandung, Indonesia; 2Department of Anatomical Pathology, Faculty of Medicine, Universitas Padjadjaran – Dr. Hasan Sadikin General Hospital, Bandung, IndonesiaCorrespondence: Pati Aji Achdiat, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran - Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, Indonesia, 40161, Tel +6281225955478 ext. 3449, Fax +62222032426, Email pati.aji.achdiat@unpad.ac.idAbstract: Anogenital warts (AGW) including multiple types of human papillomavirus (HPV) are prevalent. In this context, oncogenic HPV infection leads to anogenital cancers and the lesion is more persistent. Several research on AGW therapy with measles, mumps, and rubella (MMR) vaccine injections have been successful without adverse effects. However, the effects of MMR immunotherapy for AGW on multiple HPV infections have not been reported. This research is a case report of AGW in a 17-year-old male treated with MMR. The inclusion criteria specified young age, indicative of a strong immunological status. Meanwhile, the exclusion criteria comprised immunocompromised conditions, such as HIV confirmed to be negative. Dermatological examination showed that the pubic region and penile shaft presented 51 verrucous papules for 6 months, with histopathological results supporting the diagnosis of AGW. Polymerase chain reaction (PCR) examination reported the inclusion of HPV types 6, 11, and 16. The subcutaneous MMR vaccine was injected into the deltoid area every 2 weeks for three sessions. Meanwhile, the treatment response was assessed by counting the number and measuring the size of the lesion. After three sessions of MMR immunotherapy, there was no improvement in the size or quantity of lesions. Based on previous reports, a higher clearance rate for MMR immunotherapy was found in warts with a duration of < 6 months, while oncogenic HPV genotypes, particularly HPV type 16, take longer to clear than others. The efficacy of subcutaneous MMR injection for AGW treatment was unfavorable due to oncogenic HPV types. AGW treated with MMR immunotherapy should investigate oncogenic HPV genotype. However, further research needs to be carried out to justify this conclusion due to the limitations.Keywords: anogenital warts, immunotherapy, MMR vaccine, multiple HPV infections